Development of Network Interface Cards for TRIDAQ systems with the NaNet framework. (9th March 2017) - Ammendola, R.; Biagioni, A.; Cretaro, P.; Lorenzo, S. Di; Fiorini, M.; Frezza, O.; Lamanna, G.; Cicero, F. Lo; Lonardo, A.; Martinelli, M.; Neri, I.; Paolucci, P.S.; et al.
Abstract: NaNet is a framework for the development of FPGA-based PCI Express (PCIe) Network Interface Cards (NICs) with real-time data transport architecture that can be effectively employed in TRIDAQ systems. Key features of the architecture are the flexibility in the configuration of the number and kind of the I/O channels, the hardware offloading of the network protocol stack, the stream processing capability, and the zero-copy CPU and GPU Remote Direct Memory Access (RDMA). Three NIC designs have been developed with the NaNet framework: NaNet-1 and NaNet-10 for the CERN NA62 low level trigger and NaNet 3 for the KM3NeT-IT underwater neutrino telescope DAQ system. We will focus our description on the NaNet-10 design, as it is the most complete of the three in terms of capabilities and integrated IPs of the framework.